Youth entrepreneurship in the process of digital transformation of the economy ("Journal "U". Economy. Management. Finance.", 2023)
The article deals with the peculiarities of the development of young entrepreneurship in Russia in the context of digital transformation of the economy. In particular, the goals for the development of digital technologies are shown and the opportunities for job creation for young people are investigated. As part of the development of youth entrepreneurship, promising areas with a demand for talent have been investigated. The conclusion notes that entrepreneurial trends actively promote research activities, scientific and technological innovation, and expand the use of technology in production and life of the younger generation. It is also a good opportunity for young people in Russia to quickly master technology 4.0, to contribute to the industrialization and modernization of the country and its integration into the global economic environment.
Keywords: digital economy; Russia; youth; entrepreneurship; transformation; technology; unemployment; innovation; domestic policy; sixth technological mode; Technology 4.0